Gebrakan Merdeka Belajar Sebagai Transformasi Pendidikan Untuk Mewujudkan SDM Unggul - Ni Luh Ika Windayani; Komang Teguh Hendra Putra (STAHN Mpu Kuturan Singaraja, 2022)
Improving the quality of education in Indonesia is a national education development target. For this reason, it is necessary for the government to pay more attention to education in order to create a competitive education in the world. A new policy has been issued by Minister Nadiem, namely the independent learning curriculum that links the profile of Pancasila students as an effort to develop the potential of educators and participants in this millennial era. The implementation of the curriculum is expected to be able to create a young generation that is strong and resilient in dealing with any situation in their lives. Having character and being multitalented is the goal of the independent learning breakthrough. The concept of independent learning changes the teaching system that is usually confined to the classroom. The activeness of students in seeking new knowledge from increasingly diverse sources is expected to improve the quality of students. The concept of independent learning is related to the profile of Pancasila students, consisting of six aspects, namely: 1) Faith, Faith in God Almighty and with Noble Morals, 2) Creative, 3) Mutual Cooperation, 4) Global Diversity, 5) Critical Reasoning, 6 ) Independent.